AB0995 Clinical, therapeutic, and genetic analyses in a patient with papa syndrome complicated with inflammatory bowel disease. (15th June 2017) - Koga, T; Hidaka, Y; Fujimoto, K; Kaieda, S; Mitsuyama, K; Iwamoto, K; Fujita, K; Nishikomori, R; Hoshino, T; Ida, H
Abstract : Background: PAPA syndrome is an autoinflammatory disease linked to mutations in the PSTPIP1 gene [1]. These mutations produce a hyper-phosphorylated PSTPIP1 protein and alter its participation in the activation of the "inflammasome" [2]. PAPA syndrome is characterized by pyogenic arthritis with pyoderma gangrenosum and acne, and ususally treated with corticosteroids. Reports from the literature suggest that patients with poorly controlled PAPA syndrome may benefit from IL-1 blockade [2]; however, we cannot use these biologics for PAPA syndrome in our country. Objectives: To elucidate the pathogenesis of PAPA syndrome, we examined the clinical status and complications before and after treatment and also analyzed the PSTPIP1 gene. Methods: We herein report a 25-year-old Japanese male who suffered from recurrent arthritis in his knee and ankle joints, pyoderma gangrenosum, and acne. He had experienced melena and multiple colonic ulcers had been detected by colonfiberscopy. His ulcerations resembled ulcers associated with Crohn's disease. A histological examination was then performed for the synovium of this knee joints, skin lesions of pyoderma gangrenosum, and the colon. The genomic DNA of PSTPIP1 were analysed in both the patient and his family. We also examined the serum level of IL-1, IL-6, and TNF-α before and after treatment of biologics (adalimumab and infliximab) in this patient. Results: 1) A histological analysis revealed that a large number of neutrophils had accumulated in the skin lesions; however, very few neutrophils were detected in the pathological lesions of the knee joints and colon. 2) According to a gene analysis, we detected a novel heterozygous mutation (E101G) in the PSTPIP1 gene; however, his healthy father also had the same mutation, thus suggesting that this mutation of PSTPIP1 might not be related to his phenotype. We are searching for other affected genes besides the PSTPIP1 gene for PAPA syndrome in this case. 3) After treatment of biologics (infliximab), the clinical symptoms, such as arthritis and multiple colonic ulcers were considerably improved and the serum level of IL-6 and TNF-α were decreased in this patient. Conclusions: We herein reported a Japanese PAPA syndrome patient who was complicated with inflammatory bowel disease and had a good response to biologics. A genetic analysis suggested that this particular phenotype might not have been affected by a mutation of the PSTPIP1 gene. References: Smith EJ, Allantaz F, Bennett L, et al. Clinical, molecular, and genetic characteristics of PAPA syndrome: a review. Curr Genomica 11:519–27, 2010. Ter Haar N, Lachmann H, Özen S, et al. Treatment of autoinflammatory diseases: results rom the Eurofever Registry and a literature review. Ann Rheum Dis. 72:678–85, 2013. Disclosure of Interest: None declared